2006
DOI: 10.1021/ac0615089
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Depth Profiling Investigation of a Drug-Loaded Copolymer Utilized To Coat Taxus Express2 Stents

Abstract: The surface of a styrene-b-isobutylene-b-styrene triblock copolymer, containing a solid-phase drug, was studied by time-of-flight secondary ion mass spectrometry employing 15-keV Ga+ and 20-keV C60+ ion sources. This polymer/drug system has direct application in the cardiac stent arena, where it has been used to treat restenosis or renarrowing of arterial walls after stent or angioplasty procedures. Overall, the results illustrate the successful use of a cluster ion beam for greatly enhancing the high-mass fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…SIMS results are consistent with this (Mahoney, Patwardhan, & McDermott, 2006b). x Yes (Braun, 2006;Gillen, 2006c) …”
Section: A Backgroundsupporting
confidence: 76%
See 2 more Smart Citations
“…SIMS results are consistent with this (Mahoney, Patwardhan, & McDermott, 2006b). x Yes (Braun, 2006;Gillen, 2006c) …”
Section: A Backgroundsupporting
confidence: 76%
“…The results indicated that one could depth profile through most of these films when employing cluster primary ion beams. Braun et al was able to take this a step further and demonstrate C þ 60 depth profiling in Taxus Express 2 stents, comprised of a SIBS coating doped with paclitaxel (Braun et al, 2006). The authors were able to etch through approximately 1.5 mm of material.…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The study of surface phase transformations is of increasing interest to pharmaceutical scientists because phase transformations induced by interactions with the environment usually occur on the surface 1, 2. A few surface technologies have been applied to study pharmaceutical solids 1–15. Among them is glancing, or grazing, incidence X‐ray diffraction (GIXD).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the study of these cluster ion sources, buckminsterfullerene (C 60 + ) has received significant attention since it became a commercially available product in 2003 . Using surface analysis techniques and C 60 + ion sputtering, biological/medical and organic electronic materials have been widely studied.…”
mentioning
confidence: 99%